REKLAMASI PADA LAHAN PASCATAMBANG TIMAH DI KABUPATEN BANGKA TENGAH - , Novi Rosmarwan; , M. Sani Roychansyah, S.T., M.Eng., D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mining activities, while positively bring impact positive on economic the community, it also cause environmental problems. Attempts to restore land degradation, was done through reclamation activity. The research aims to: (1) describe the reclamation of tin mined lands activities